Exploration of Quantitative Sensory Testing in Latent Trigger Points and Referred Pain Areas. Issue 5 (May 2018) - Ambite-Quesada, Silvia; Arias-Buría, José L.; Courtney, Carol A.; Arendt-Nielsen, Lars; Fernández-de-las-Peñas, César
Abstract : Objective: The objective of this study was to investigate somatosensory nerve fiber function by applying different quantitative sensory testing including thermal, mechanical, and vibration thresholds over latent trigger points (TrP) and in its associated referred pain area. Methods: A total of 20 patients with unilateral latent TrPs in the extensor carpi radialis brevis were included. Warmth detection threshold (WDT), cold detection threshold (CDT) and heat/cold pain thresholds (HPT, CPT), mechanical detection (MDT) and pain (MPT) thresholds, vibration threshold (VT), and pressure pain thresholds (PPT) were blinded assessed over the TrP, in the referred pain area, and in the respective contralateral mirror areas. A multilevel mixed-model ANOVA with site (TrP, referred pain area) and side (real or contralateral) as within-patient factors and sex as between-patients factor was conducted. Results: No significant differences for thermal detection (WDT, CDT) or thermal pain thresholds (HPT, CPT) were found (all, P s>0.141). The assessments over the TrP area showed lower PPT and MDT compared with the mirror contralateral TrP area ( P <0.05). MDT were higher ( P =0.001) but PPT ( P <0.001) and MPT ( P =0.032) were lower over the TrP area and contralateral mirror point compared with their respectively referred pain areas. Finally, VT was higher over the TrP area than in the referred pain area and over both mirror contralateral points. Discussion: Assessing sensory changes over latent myofascial TrPs reveal mechanical hyperesthesia, pressure pain hyperalgesia, and vibration hypoesthesia compared with a contralateral mirror area.